Problem-Based Learning with Argumentation as a Hypothetical Model to Increase the Critical Thinking Skills for Junior High School Students (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2020)
The Problem-Based Learning with Argumentation (PBLA) model is a development model of Problem-Based Learning (PBL) added to the Toulmin Argumentation activity to increase the critical thinking skill in junior high school. The research aims to determine the feasibility of PBLA in terms of its validity and effectiveness. The research samples are two groups of students (class 1 and class 2) with 26 students in each class. Before learning to use PBLA, each class was given a pretest, and after learning to use PBLA were also given a posttest. PBLA validity data were obtained through validity sheets and analyzed through expert agreement. PBLA effectiveness data was obtained through critical thinking skill tests and analyzed by paired t-test, n-gain, and two-average similarity test. The results showed that the content validity and the construct validity categorized as valid with a score of 3.5 and 3.3. The reliability scores obtained are 77.10% and 77.67%. The critical thinking skill data showed a significant increase in critical thinking skill at Î± = 5%, the average n-gain was categorized high, and there was a similarity in increasing critical thinking skills for the two classes. In conclusion, PBLA is effective in increasing critical thinking skills for junior high school students